2010
DOI: 10.1111/j.1600-0447.2009.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unipolar psychotic depression: a randomized, double‐blind study comparing imipramine, venlafaxine, and venlafaxine plus quetiapine

Abstract: That unipolar psychotic depression should be treated with a combination of an antidepressant and an antipsychotic and not with an antidepressant alone, can be considered evidence based with regard to venlafaxine-quetiapine vs. venlafaxine monotherapy. Whether this is also the case for imipramine monotherapy is likely, but cannot be concluded from the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 30 publications
1
71
1
1
Order By: Relevance
“…There is a growing body of evidence from recent randomized controlled trials, suggesting that the combination of an antidepressant and an antipsychotic is the superior pharmacological treatment approach in patients with PD [85,86,87,88]. In agreement with these findings, most major expert guidelines on PD recommend either electroconvulsive therapy or the combination of an antidepressant and an antipsychotic as first-line treatment [89,90,91].…”
Section: Introductionmentioning
confidence: 55%
“…There is a growing body of evidence from recent randomized controlled trials, suggesting that the combination of an antidepressant and an antipsychotic is the superior pharmacological treatment approach in patients with PD [85,86,87,88]. In agreement with these findings, most major expert guidelines on PD recommend either electroconvulsive therapy or the combination of an antidepressant and an antipsychotic as first-line treatment [89,90,91].…”
Section: Introductionmentioning
confidence: 55%
“…Wijkstra and colleagues 43 reported on a double-blind, randomized controlled study of 122 hospitalized patients (aged 18-65 years) with psychotic depression at 8 sites in the Netherlands. The patients were treated for 7 weeks with imipramine (n = 42), venlafaxine (n = 39), or the combination of venlafaxine and quetiapine (n = 41).…”
Section: Newer Medicationsmentioning
confidence: 99%
“…The authors concluded that the combination of venlafaxine and quetiapine was more effective than venlafaxine alone on the primary outcome measure (response) and was well tolerated. 43 Sertraline Plus Olanzapine. The largest study to date, the NIMH Study of the Pharmacotherapy of Psychotic Depression (STOP-PD) reported results that indicated that the combination of an antidepressant and an atypical antipsychotic medication was more efficacious than monotherapy with the atypical antipsychotic.…”
Section: Newer Medicationsmentioning
confidence: 99%
“…As discussed earlier, the recent RCT comparing the TCA imipramine head-to-head with venlafaxine is hard to interpret because of conflicting data on response and remission (34).…”
Section: Node 7: Tca Snri or Ssri Monotherapy?mentioning
confidence: 99%